The crown lengthening double guide and the digital Perio analysis. Issue 1 (4th May 2022) - Coachman, Christian; Valavanis, Konstantinos; Silveira, Fernanda Camargo; Kahn, Sergio; Tavares, Alexandra Dias; Mahn, Eduardo; Parize, Hian; Saliba, Felipe Miguel P.
Abstract: Objective: This article describes a surgical crown lengthening double guide, which was digitally obtained to improve diagnosis, treatment outcome, and follow‐up. Clinical considerations: The rehabilitation of anterior dental esthetics should involve interdisciplinary and facially driven planning for achieving pleasant long‐term outcomes. Surgical crown lengthening is one of the most common periodontal surgery, which can be assisted by digital tools to improve surgical planning and follow‐up. Conclusion: The double guide for surgical crown lengthening allows the proper management of hard and soft tissues for achieving a predefined goal based on biological requirements and facially driven planning. In addition, the digital quality control allows the follow‐up compared with the pre‐operative condition and planned treatment plan. Clinical significance: The use of digital tools allow the clinician to develop a facially driven planning with proper communication with the team and patient, leading to a shorter, more predictable, and less invasive surgical technique, reducing postoperative inflammation and increasing patient comfort.